CAT: a context aware teller for supporting tourist experiences. (22nd October 2019) - Casillo, Mario; Colace, Francesco; Santo, Massimo De; Lemma, Saverio; Lombardi, Marco
The aim of this paper is the introduction of a methodology for the dynamic creation of an adaptive generator of the stories related to a tourist context. The proposed approach selects the most suitable contents for the users and builds a context aware teller that can support them during the exploration of the context making it more appealing and immersive. The tourist can use the system by a hybrid app. The dynamic context aware telling engine grabs the contents from a knowledge base that contains data coming both from the knowledge base and from the web. The user profile is updated thanks to information obtained during the visit and from the social networks. A case study and some experimental results are presented and discussed.